Anatomical and Functional Outcome of Scleral Buckling and Primary Vitrectomy in Rhegmatogenous Retinal Detachment - Nashrul Ihsan; Ari Djatikusumo; Andi A.Victor; Elvioza; Gitalisa Andajani; Anggun R. Yudantha; Mario M. Hutapea (Fakultas Kedokteran Universitas Kristen Indonesia, 2014)
Abstract Retinal detachment is a serious sight-threatening condition, which needs a prompt treatment. Recently, pars plana vitrectomy (PPV) has been frequently used than scleral buckling (SB) although the advantages of PPV over SB had never been proven. To compare anatomical and functional outcomes, as well as complications of SB vs. primary PPV as the initial surgery in rhegmatogenous retinal detachment, a literature study was carried out for journal articles indexed by the PubMed. We included studies (interventional or observational) that reported the use of primary PPV vs. SB in retinal detachment. We did not restrict the search by the lens status. We excluded studies that were not reported in English and could not be accessed. Out of 44 articles identified, only seven articles were eligible. In most studies, the rates of retinal attachment after the first surgery of both techniques were similar (p>0.05). Only two studies reported significantly better primary anatomical success in PPV than SB (p=0.0002 and p=0.037). Both techniques also showed functional success based on the best corrected visual acuity (BCVA) results, with three studies found that PPV had a significantly better final BCVA (p=0.03, p=0.0005, p<0.05). The complication of these two techniques could not be compared. Retinal re-detachment, choroidal detachment, proliferative vitreoretinopathy (PVR) progression and infection were reported in SB group. Meanwhile, higher intraocular pressure, retinal re-detachment, PVR, epiretinal membrane (ERM), macula pucker, and iatrogenic break were reported in PPV group. Both surgical techniques gave good results in visual function (LogMar <1.00) and quite the same in primary anatomical success.Key words: pars plana vitrectomy, rhegmatogenous retinal detachment, scleral buckling Abstrak Ablasio retina merupakan suatu kedaruratan mata yang membutuhkan tata laksana segera. Dewasa ini, vitrektomi pars plana (pars plana vitrectomy/PPV) lebih sering digunakan dibandingkan scleral buckling (SB), meskipun kelebihan PPV dari SB belum pernah dibuktikan. Untuk membandingkan luaran anatomi dan fungsi, serta komplikasi SB dan PPV primer sebagai tata laksana bedah inisial pada ablasio retina regmatogenosa, dilakukan pencarian literatur menggunakan database PubMed. Kriteria inklusi adalah artikel yang melaporkan hasil PPV primer vs. SB pada ablasio retina. Seleksi tidak dibatasi oleh status lensa. Kriteria eksklusi adalah artikel yang tidak menggunakan Bahasa Inggris dan tidak dapat diakses. Dari 44 artikel yang teridentifikasi, tujuh artikel memenuhi kriteria. Tingkat perlekatan retina setelah operasi pertama pada kedua teknik setara hampir pada semua studi (p>0,05). Hanya dua studi melaporkan keberhasilan anatomis primer yang secara signifikan lebih baik pada PPV (p=0,0002 and p=0,037). Kedua teknik juga menunjukkan keberhasilan fungsional dilihat dari best corrected visual acuity (BCVA), dengan tiga studi melaporkan BCVA yang secara signifikan lebih baik pada PPV (p=0,03, p=0,0005, p<0,05). Komplikasi kedua teknik tidak dapat dibandingkan. Pada kelompok SB dilaporkan terjadinya retinal re-detachment, choroidal detachment, prolifestive vitreoretinopathy progresif (PVR) dan infeksi. Sementara itu, dilaporkan peningkatan tekanan intraokular, retinal re-detachment, PVR, epiretinal membrane (ERM), macula pucker, dan robekan iatrogenik pada kelompok PPV. Kedua teknik bedah memberikan hasil akhir tajam penglihatan yang baik (LogMar <1.00) dan keberhasilan anatomis primer yang relatif sama.Kata kunci: ablasio retina regmatogenosa, scleral buckling, vitrektomi pars plana.